Barriers to civic engagement in the metropolitan region of Ribeirão Preto - Nogueira, Caroline Kalil; Meek, Jack (Revista Científica Foz, 2018)
This work constitutes an investigation into the Metropolitan Region of Ribeirão Preto, currently considered as the "Brazilian Capital of Agribusiness". The paper is divided into three sections which address the Brazilian institutional aspects and their application to the specified region, as well as socioeconomic aspects of regional development. The objective is to demonstrate that there are obstacles to collaborative participation in public administration and also barriers to greater regional integration, given that Ribeirão Preto is both an export base hub and an area of influence in the São Paulo macro-metropolis (São Paulo extended metropolitan complex). The theoretical foundation involved in this study is based on the constitutional norms that guide and determine competence in the scope of political institutions, as well as federal entities. In addition, a spatial approach was chosen within Economic Geography, converging to the issue of civic participation in Brazil, both in legal and socio-political aspects, considering historical and cultural elements, according to the studies of historian Sérgio Buarque de Holanda. Despite the introductory nature of this work, its importance lies in identifying socio-political boundaries and barriers to economic development, since public policies aimed to this end in Brazil have proven to be punctual and ineffective for the solution of asymmetries and the improvement of the quality of life of the population.